1995
DOI: 10.1051/rnd:19950207
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gastrointestinal permeability to small marker probes in the preruminant calf

Abstract: Summary ― The intestinal permeability to markers was assessed in preruminant calves fed different milk substitutes containing skimmed milk powder or whey and soyabean products of differing antigenic activity as the protein sources. In Experiment 1, the 6 h urinary excretion of lactulose transiently decreased with the antigenic soyabean product but not that of sucrose or D -mannitol. In Experiment 2, the 6 h urinary excretion of sucrose and D -mannitol averaged 1-3%, regardless of age and dietary treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
7
2
Order By: Relevance
“…Serum lactulose:d-mannitol ratios found herein are within the range of those reported by Branco Pardal et al (1995) but greater than those reported by Klein et al (2007Klein et al ( , 2008. Intestinal integrity can be estimated by the serum lactulose:d-mannitol ratio, which is based on the assumption that a normal villus may take up many small but few large molecules.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Serum lactulose:d-mannitol ratios found herein are within the range of those reported by Branco Pardal et al (1995) but greater than those reported by Klein et al (2007Klein et al ( , 2008. Intestinal integrity can be estimated by the serum lactulose:d-mannitol ratio, which is based on the assumption that a normal villus may take up many small but few large molecules.…”
supporting
confidence: 78%
“…The principle of the test is based on the as-sumption that the monosaccharide d-mannitol passes the intestinal epithelia through small pores on the apical surface of enterocytes (transcellularly), whereas the disaccharide lactulose passes the epithelia through the tight junctions located between the epithelial cells (paracellularly). However, differently from previous studies that measured intestinal permeability of calves by quantifying d-mannitol and lactulose in urine (Branco Pardal et al, 1995;Klein et al, 2007Klein et al, , 2008, in the present study both saccharides were quantified in serum. Even though extracting blood is an invasive technique, in farm animals it is more practical than collecting urine.…”
Section: Intestinal Permeabilitymentioning
confidence: 76%
“…Recoveries of lactulose and d-mannitol as well as IP index found herein for the 6-h collection are in the range of those reported by Klein et al (2007Klein et al ( , 2008, but lower than those reported by Branco Pardal et al (1995;Table 4). For the 6-h collection period, calves in the current study had an IP index between 0.23 and 0.40.…”
Section: Discussioncontrasting
confidence: 65%
“…The solutions were mixed together with the morning CMR meal at 3 and 7 wk of age. Urine was quantitatively collected during 2 periods; 0 to 6 h and 6 to 24 h after marker administration according to Branco Pardal et al (1995). Urine was directly acidified to pH ≤2 with sulfuric acid to prevent microbial activity.…”
Section: Measurementsmentioning
confidence: 99%
“…44 The D-xylose absorption test originally was introduced as a diagnostic procedure for malabsorption syndrome in humans. 45 The test has been applied in horses, 46 adult cattle, 26 suckling calves, [47][48][49][50][51][52][53][54][55][56] and adult sheep. 40,57 Like other sugars, D-xylose is absorbed by active and passive transport mechanisms in the duodenum and proximal jejunum, with marked species differences in the efficiency of absorption.…”
Section: Discussionmentioning
confidence: 99%